The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3346/jkms.2015.30.3.296
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Serum Luteinizing Hormone to Folliclestimulating Hormone Ratio and the Anti-Müllerian Hormone Levels in Normo-ovulatory Women

Abstract: Serum anti-Müllerian hormone (AMH) levels are regarded as an age-specific marker for predicting the ovarian reserve in women of reproductive age. Some studies have shown that the luteinizing hormone (LH)/follicle stimulating hormone (FSH) ratio can be used as a predictor of ovarian reserve. The purpose of this study was to assess the variation of LH/FSH ratio with aging and to evaluate the correlation between serum LH/FSH ratio and AMH levels as a predictor of the ovarian reserve in normo-ovulatory women. We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
5
10
0
1
Order By: Relevance
“…After controlling for age and BMI factors, the serum AMH levels had only negative significant correlation with FSH and LH; suggesting age-related reduced testicular function, that is in agreement with previous reports both in male [42] and female populations [43]. …”
Section: Discussionsupporting
confidence: 92%
“…After controlling for age and BMI factors, the serum AMH levels had only negative significant correlation with FSH and LH; suggesting age-related reduced testicular function, that is in agreement with previous reports both in male [42] and female populations [43]. …”
Section: Discussionsupporting
confidence: 92%
“…Clinicians commonly use LH:FSH ra o in assessing the polycys c ovarian syndrome (PCOS) although we could not [22][23][24] prove the sufficient u lity of it in our study. In infer lity, researchers have shown the highest correla on of LH:FSH ra o with clinical pregnancy over other measures of ovarian 5,[25][26][27] reserve.…”
Section: Discussionmentioning
confidence: 99%
“…Human biologists describe it as a quan ty of ovarian follicular cohort 4 and quality of oocytes. Assessing an individual's ovarian reserve comprise with evalua on of certain variables like age, follicle s mula ng hormone (FSH), leu nizing hormone 5 (LH), LH:FSH ra o and prolac n (PRL) as main task. Recently, scien sts have studied serum an -mullerian hormone 6 (AMH) as poten al test for ovarian reserve.…”
Section: Introductionmentioning
confidence: 99%
“…Interest in research on prediction of ovarian response in assisted reproductive techniques has increased in recent years. Lee et al [49] studied variations of AMH FSH, LH hormones in Korean women. This study described that basal LH/FSH ratio and AMH level has a valuable clinical meaning as an important predictor of ovarian response in IVF patients [49].…”
Section: Evaluation Of Ovarian Reserve Markers In Women With Reproducmentioning
confidence: 99%
“…Lee et al [49] studied variations of AMH FSH, LH hormones in Korean women. This study described that basal LH/FSH ratio and AMH level has a valuable clinical meaning as an important predictor of ovarian response in IVF patients [49]. Furthermore, Cohen et al [10], Keane et al [50], Zebitay et al [51], Zheng et al [52], Goswami et al [53] and Spressão et al [54] have shown the important clinical application of AMH and AFC in the fertility counseling on infertile women correlated with pregnancy rates, live birth rates, number of retrieved eggs, fertilization rates and embryo development rates [10,[50][51][52][53][54].…”
Section: Evaluation Of Ovarian Reserve Markers In Women With Reproducmentioning
confidence: 99%